The distribution of Pb(II)/Cd(II) adsorption mechanisms on biochars from aqueous solution: Considering the increased oxygen functional groups by HCl treatment - Wu, Jiawen; Wang, Tao; Zhang, Yongsheng; Pan, Wei-Ping (Bioresource technology, 2019)
[Display omitted] •The content of OFGs increased on the biochars after HCl treatment.•OFGs(COOH and OH) could complex with Pb(II)/Cd(II) as adsorption sites.•Qf was determined more accurately by the consumption amount of OFGs.•Pb/Cd-O accounts for more than 80% on the adsorption of Pb(II)/Cd(II). The adsorption mechanisms of Pb(II) and Cd(II) in aqueous solution using camellia seed husk biochars pyrolyzed at different temperatures were studied. The adsorption of Pb(II) and Cd(II) on biochars are mainly controlled by ion exchange, oxygen functional groups (OFGs) complexation, Pb(II)/Cd(II)–π interactions, and precipitation with minerals. Compared to the raw biochars, both carboxyl and phenolic hydroxyl groups increased in the biochars washed with HCl. However, the previous research ignored the effect of the increased OFGs. Thus, a revised method was proposed from this study to more accurately calculate the contribution of four different mechanisms. Precipitation with minerals was the dominant mechanism for Pb(II) and Cd(II) removal, accounting for 80.61–89.03% and 53.57–75.84%, respectively, of the total adsorption as the pyrolysis temperature increased from 300 °C to 700 °C. As for oxygen functional groups complexation, the percentage of Pb(II) and Cd(II) removal were 4.76–8.55% and 11.34–29.59%, respectively.